Is a gender perspective necessary for understanding the economy?. Issue 1 (2nd October 2018) - Ghosh, Jayati
Abstract: The articles in this issue ask what we are missing when we study an economy without taking into account the way in which gender relations impact its functioning, at both micro and macro levels. They open the way for fresh thinking on the interplay between gender relations and capitalist economic dynamics.